Chicago's Pride: The Stockyards. Packingtown, and Environs in the Nineteenth Century - Goheen, Peter G. (Labour / Le Travail, 1989)
The article reviews the book, "Chicago's Pride: The Stockyards. Packingtown, and Environs in the Nineteenth Century," by Louise Carroll Wade.
Keywords: CHICAGO'S Pride: The Stockyards, Packingtown & Environs in the 19th Century (Book); LABOR market; Nonfiction; REVIEWS; WADE, Louise Carroll; books